Augustine's appeal to Cyprian in the Donastist and Pelagian controversies a study of the legitimacy of the use of authority in two controversies in Roman North African. - Gaumer, Matthew Alan; Lamberigts, Mathijs; KU Leuven. Faculteit Theologie en Religiewetenschappen (Leuven KU Leuven. Faculteit Theologie en Religiewetenschappen, 2012)
Central in this research proposal is the reception of Cyprian in Augustine and the Donatists in the Donatist Controversy and in Augustine and in a lesser degree by the Pelagians in the Pelagian Controversy. All parties in both controversies refer positively to Cyprian and consider him as a iudex, vested with auctoritas to be consulted in exemplary and doctrinal matters. The basic question of this research is: if/where/how is the Cyprian profile respectively in both camps different and/or similar and if/where/how Augustine's Cyprianic profile is identical or different in both controversies? Which elements play a role in these similarities in/or differences and can we observe an evolution in Augustine? What does a comparative analysis teach us about the concepts of auctoritas, novitas and traditio in Augustine and his opponents.
Diss. doct
Keywords: Theses; 276 =71 AUGUSTINUS -- Latijnse patrologie--AUGUSTINUS